Age and Gender: Affecting the Positive Rates of Serum PAB and ANCA in Patients with Inflammatory Bowel Disease - Qingquan Chen; Shirong Huang; Yue Wu; Shuyu Zhang; Qicai Liu; Min Chen (Gastroenterology Research and Practice)
Inflammatory bowel disease (IBD) is a group of immune-mediated conditions. Immune activity is varied by age and gender. The present study is aimed at investigating the effect of age and gender on the positive rates of anti-Saccharomyces cerevisiae antibodies (ASCA), anti-neutrophil cytoplasmic antibodies (ANCA), anti-intestinal goblet cell antibodies (GAB), and antibodies to exocrine pancreas (PAB) in IBD patients. A total of 1871 hospitalized patients with confirmed IBD were included in this study. Sera were obtained from each subject for antibody measurement by indirect immunofluorescence assay. The positive rates of ANCA IgG and IgA were higher in female patients than those in male patients (P<0.001) while the positive rate of PAB IgG was just reversed (P<0.001). Moreover, the median ages of patients with positive ANCA IgG and IgA were higher than patients with negative antibodies (P=0.0019 and P=0.0110, respectively), while the median ages of patients with positive PAB IgG and IgA were significantly lower than patients with negative PAB (P<0.0001). The serum levels of ANCA IgG and IgA were potentiated in old female patients, while serum PAB IgG was easy to be detected in the young male patients with IBD.